Teaching and preaching Second Corinthians - Thompson, James W. (Proclaimation preaching the New Testament, 2021)
"While the commentaries and articles on 2 Corinthians focus on the world behind the text, giving attention to the identity of Paul's opposition and questions about the letter's composition, few scholars have bridged the gap between the exegesis of 2 Corinthians and the sermon. The issue of what constitutes legitimate ministry, the focus of 2 Corinthians, is a pressing issue today for churches as they face an identity crisis. Paul confronts opponents who judge him by secular standards of ministry, offering an alternative that is based on the cross. Second Corinthians offers an insight into both the nature of pastoral ministry and the mission of the church. This book draws parallels between Corinth and the contemporary situation of the church. The exegetical insights demonstrate the primary focus of the passage as the basis for the preaching text. This book demonstrates a full awareness of current scholarship on 2 Corinthians and offers hermeneutical and homiletical guidance for addressing these issues today."